The Effect Of Using Augmented Reality Media One The Learning Results of The ‘Caping Ngancak’ Dance for Grade V Students At Sdn 2 - Cut Rifhka; Aida Fitri; Intan Safiah (Universitas Negeri Semarang, 2023)
In learning arts and culture, there are still many students who do not understand traditional dance material, especially the ‘caping ngancak’ dance. The implementation of learning implemented by teachers is still teacher-centered, teachers do not involve students enough so that there are still many students who are less active. For this reason, it is necessary to implement learning that can make students active in learning arts and culture. So a medium was used in this research, namely Augmented Reality media. The formulation of the problem in this research is